Pelatihan Virtual Manajemen Strategi Pembelajaran Bagi Tenaga Pendidik di Masa Pandemi Covid-19 - Krida Puji Rahayu; Rudi Sanjaya; Lativa Lativa; Nurmono Nurmono; Muhamad Restu Wijaya (Jurnal Abdi Masyarakat Humanis, 2021)
PKM between the ranks of teachers and the principal of SMPN 12 Kota Tangerang Selatan with lecturers at Pamulang University is well established. On the basis of regulations from the Central government and the Banten local government due to the Covid-19 Pandemic, all schools including SMPN 12 Kota Tangerang Selatan implemented online learning during the pandemic. Schools dismiss students as a form of emergency decision to prevent the spread of the virus. Many families in Indonesia still do not understand how to do School From Home (SFH). On the other hand, school is a medium of interaction between students and teachers to improve intelligence, skills and affection between them. However, it had to stop functioning because of the pandemic. Based on the findings of this case, the problem arises how teachers are able to demonstrate the ability to utilize technological media and be able to present planned and effective learning within limited time. How the teacher is able to unite the perceptions and concentrations of students who are far apart. Also how teachers are able to convey messages to students to be strong children considering the conditions where society is being tested physically and mentally due to the spread of Covid-19 which has an impact on student learning. Thus, a solution emerged by implementing strategic management for educators in teaching their students during this pandemic. Keywords: Teacher ability, online learning, Covid-19 impact